The Lasting Effects of Childhood Trauma: Causes, Impacts, and Intervention Strategies - Michelle Indarto Susanto; Augustina Sulastri (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
Childhood trauma is mainly caused by events that threaten a child’s growth, and development. It has a significant impact on children’s well-being. The high suicide rate comes from trauma factors that trigger self-harming behavior. Children who experience trauma are at risk of developing anxiety, eating disorders, sleep disorders, and suicidal thoughts. This study aimed to investigate the causes, and consequences of childhood trauma, as well as potential interventions for parents, and institutions. Using a scoping review method, we analyzed existing literature to identify the root causes of childhood trauma. Our findings suggest that psychological distress in children can persist into adulthood, leading to changes in attitudes, and behavior. Fortunately, psychological based interventions, such as Play Therapy, Forgiveness, and Self Resilience strategies can help mitigate the effects of childhood trauma.